Engaging with students as partners in education-space design - Streule, Mike; McCrone, Luke; Andrew, Yasmin; Walker, Craig (International Journal for Students as Partners, 2022)
Engaging with Students as Partners (SaP) in areas of curriculum design and pedagogic consultancy is relatively well established. Here we present a case study of two recent projects at Imperial College London, a research-intensive science, technology, engineering, mathematics, and medicine (STEMM) university, that have extended the SaP model to the design and delivery of modifications to education spaces. Using a research-informed approach and tested method ensured that the students remained active throughout the “twists and turns” of the project, rather than the more traditional snapshot student-consultation approach often taken early in the design process. Students experienced authentic partnership with staff, the space, and their department/institution more broadly whilst staff acknowledged that the quality of outputs significantly exceeded expectations at a fraction of the cost of engaging external design consultants. More broadly, projects such as these establish precedents for a more ambitious institutional approach to working with students as partners.